Student-teacher use of different teaching methods during the application period (Journal of the College of Basic Education, 2023)
Those interested in teaching mathematics notice that many studies and researches have concluded that a teaching method is preferred over another method in teaching the subject in general, without taking into account the characteristics of the unit of knowledge of the subject, or the characteristics of the target group of learners.